Vaccination of pneumococcal infection in patients with systemic lupus erythe matosus and antiphospholipid syndrome: experience of 6 years of use - G. M. Tarasova; B. S. Belov; T. M. Reshetnyak; M. V. Cherkasova (Научно-практическая ревматология, 2023)
Infections remain one of the main causes of morbidity and mortality in patients with immuno-inflammatory rheumatic diseases. Objective – to study the efficacy, immunogenicity and safety of the 23-valent polysaccharide pneumococcal vaccine (PPV-23) in patients with systemic lupus erythematosus (SLE) and antiphospholipid syndrome (AРS). Materials and methods. 91 patients were included in the study: 78 with SLE, of which 18 (23 %) – with secondary AРS, 13 – with primary AРS. 85 patients received immunosuppressive therapy, including 30 – genetically engineered biological drugs (bDMARD); 23 – anticoagulants. PPV-23 was administered subcutaneously, patients were observed for a year after vaccination. Results. Local reactions were observed in 49% of patients with SLE and secondary AРS, in 23% of patients with primary AРS. General reactions were noted in isolated cases, were short-term and did not require additional prescriptions. During the follow-up period, no exacerbations of SLE, relapses of thrombosis and thromboembolism associated with vaccination were detected; no development of new autoimmune diseases was registered. 10 (13%) patients with SLE were immunized against the background of high activity of the disease, no adverse reactions were recorded. In some patients, a transient increase in a-DNA and ANF was observed during the year without signs of exacerbation of the disease. 56% of patients with SLE and secondary AРS, 15.4% with primary AРS were “responders” to the vaccine. There was no negative effect on the immune response of the dose of GC >10 mg/day, age, duration and activity of the disease. With the treatment of bDMARD, a full-fledged vaccine response was recorded much less frequently than with standard therapy (38% and 67.4%, respectively; p=0.01). After vaccination, there was a significant decrease in the number of lower respiratory tract infections (LRTI) (p=0.0001), including community-acquired pneumonia (PN) (p=0.03) and acute bronchitis (p=0.04), ENT infections (p=0.001). In the treatment of rituximab (RTM), compared with belimumab (BLM), a greater number of LRTI was observed, mainly due to PN. After vaccination on RTM therapy, the number of INDP in general (p=0.008) and PN in particular (p=0.03) decreased, isolated cases of LRTI and ENT organs were recorded on BLM therapy. Within 4–6 years after vaccination, 30 patients with SLE retained the clinical effect of vaccination, while immunogenicity decreased to 18%. Conclusion. Safety, sufficient immunogenicity, and clinical efficacy of PPV-23 in patients with SLE and AРS have been shown. The use of bDMARD reduces the vaccine response. Immunization performed prior to or during treatment with bDMARD lasting <1 year increases the number of vaccine responders.